Effect of Myracrodruon urundeuva and Qualea grandiflora extracts on viability and activity of microcosm biofilm and prevention of enamel demineralization in vitro - Pires, Juliana Gonçalves (2018)
The objective of this study was to evaluate the antimicrobial and anti-caries effects of two plant extracts. The first chapter dealt with a review of the literature whose objective was to discuss the antimicrobial potential of Brazilian natural agents on the biofilm related to dental caries and gingivitis/periodontal disease. The research of the articles was carried out using PubMed. We found a total of 23 papers. Most of the studies were performed using planktonic microorganisms or under clinical trials. Nineteen articles were focused on cariogenic bacteria. From these nineteen articles, eleven were also about periodontopathogenic bacteria. Four studies addressed only periodontopathogenic bacteria. The most tested Brazilian natural agents were green propolis, essential oils of Lippia sidoides and Copaifera sp. Most of the tested agents showed similar results when compared to positive control (essential oils and extracts) or better effect than negative control (green propolis). More studies involving protocols closer to the clinical condition and the use of response variables that allows understanding the mechanism of action of natural agents are necessary before the incorporation of these natural agents into dental products. The second chapter aimed to test the effect of the hydroalcoholic extracts of Myracrodruon urundeuva All. and Qualea grandiflora Mart. leaves on the viability of the microcosm biofilm and on the prevention of enamel demineralization. The microcosm biofilm was produced on bovine enamel, using human saliva pool mixed with McBain saliva (0.2% sucrose) for 14 days. The biofilm was treated daily with the extracts for 1 min. M. urundeuva at 100, 10 and 0.1 g/ml and Q. grandiflora at 100 and 0.1 g/ml reduced cell viability similarly to the positive control and significantly more than negative control. M. urundeuva at 1000, 100 and 0.1 g/ml were able to reduce the counting formation unit-CFU counting of lactobacilli sp. and Streptococcus mutans, while Q. grandiflora at 1000 and 1.0 g/ml significantly reduced the S. mutans CFU counting. On the other hand, the natural extracts did not reduce the production of extracellular polyssacharides, lactic acid and the development of enamel caries lesions. The third chapter aimed to evaluate the effect of hydroalcoholic extracts of M. urundeuva and Q. grandiflora (alone or combined) on the viability of S. mutans biofilm and the prevention of enamel demineralization. S. mutans strain (ATCC 21175) was reactivated in BHI broth. Minimum inhibitory concentration, minimum bactericidal concentration, minimum biofilm inhibitory concentration and minimum biofilm eradication concentration were determined to choose the concentrations to be tested under the biofilm model. S. mutans biofilm (5x105 CFU/ml) was produced on bovine enamel using McBain saliva with 0.2% sucrose for 3 days. The biofilm was treated daily with the extracts for 1 min. M. urundeuva (isolated or combined) at concentrations equal or higher than 0.625 mg/ml was able to reduce the bacteria viability, whereas Q. grandiflora extract alone showed antimicrobial effect at 5 mg/ml only (p<0.05). On the other hand, none of the extracts was able to reduce the development of enamel caries lesions. Despite the tested natural extracts have antimicrobial effect; they are unable to prevent caries in enamel.